Lake highstands in the northern Kalahari, Botswana, during MIS 3b and LGM. (30th August 2020) - Wiese, Robert; Hartmann, Kai; Gummersbach, Venise S.; Shemang, Elisha M.; Struck, Ulrich; Riedel, Frank
Abstract: The interpretations of late Quaternary climate variation in the Kalahari are controversial. Only few speleothem humidity records do exist and reconstruction of aridity periods using aeolian sediments is challenged by considerable dating uncertainties. On the other hand studies on the large structural lake basins of the Kalahari have to cope with tectonics and the active catchment being far in the north, in a different climate zone. Thus hydrological signals from such palaeolakes may not or only partly reflect Kalahari palaeoclimate. The sediments of a regional drainage basin, west of the Tsodilo Hills, northern Kalahari, archive hydrological signals not superimposed by remote river catchment and tectonics. A ca. 3 m thick sediment profile near the palaeoshore of the former lake exhibits two lake highstands dated to MIS 3b and LGM. Geomorphological studies, fossil aquatic assemblages, their comparison to modern analogues and geochemical analyses, including sclerochronological stable isotope patterns from gastropod shells, suggest relatively deep, freshwater to oligohaline, open-basin lake periods. The data indicates that the climate was more humid than today, with two intra-annual rainfall maxima during the LGM, but likely under temperature regimes similar to modern times. The lake highstands were probably in phase with an inter-hemispheric Atlantic climate seesaw, which may imply that the main moisture source was rather the southern Atlantic than the Indian Ocean.